(untitled) (Perner’s Contacts, 2016)
The paper presents the draft model for the stocks level optimization with utilization of the suitable way of their purchase. Determination of the optimization criteria is considered to be the necessary step. They are designed based on the definition of the aspects affecting the determining the way of purchase. In this paper, the algorithm for the determining the suitable way of purchase is proposed as well. This algorithm takes into consideration the specific criteria and draft model for the stocks management. Then, the particular examples of costs decreasing and decreasing the risk of the stocks shortage with the utilization of the designed model comparing the implementation of existing models are described in the paper.